Topics regarding access to european information institutions: European Union so close and yet so far - Terra, Ana Lúcia (2015)
From the 1990s, the Parliament, the Council and the European Commission adopted a new approach to disclosure of their working papers. Legal instruments to regulate and allow a fairly broad access to internal working documents of these institutions were created. European institutions also exploited the potential of Information and Communication Technologies, developing new instruments to register the documents produced and make them accessible to the public. The commitment to transparency sought to shows a more credible European government, and reduces the democratic deficit. However, the data analysis regarding access to EU institutions documents shows that general public is still far from direct contact with European bodies.